Spying eyes - Holder, Nancy; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1998)
Sabrina is psyched when her Aunts tell her about the next witch holiday: All-You-Can-Cast Day, when she wants without worrying about all the usual rules. The next morning, all the spells will reverse and the day will begin again, with the mortals none wiser. After her refreshing day of freedom, Sabrina is ready for normal life again -- until she discovers that one of her spells survived the night...but which one? Meanwhile, a team of government scientists has descended on Westbridge, searching for signs of magic. Can Sabrina throw the men in black off the trail... before they spy her spell?
"An Archway paperback."
"Based on the hit TV series"--Cover.
Keywords: Sabrina the Teenage Witch (Fictitious character) -- Fiction; Witches -- Fiction; Occult fiction; Young adult fiction